A Call for New Religious Discourse in a Changing World - QANSO, Wajih (Proche-Orient Chrétien, 2019)
Abu-Dhabi’s declaration emphasizes on the fast-changing nature of the world, as new elements penetrate into our everyday lives, thus veering individuals, groups, and societies, to unprecedented human life form, status, and relations. The declaration suggests that the existence of the human race is not governed by the prevailing political systems, and the inherited societal institutions and relations, and that the manifestation and aspiration of human life are not bounded by current cultures, religions, and nations. History has not yet consumed all human possibilities. [...]